The Phenomenology of the Happy Host: An Interpretative Phenomenological Analysis and Autoethnographic Study of Alterity in the Hospitality Industry - Pitiquen, Kirk (Auckland University of Technology, 2025)
This personal exploration examines the distinct qualities and perspectives of a joyful host in the food and beverage industry within a commercial hospitality venue. It highlights the necessity of enriching the emotional experiences of both guests and oneself during service encounters. This study examines the significant experiences that enhance the well-being of individuals and those around them, revealing a unique phenomenon of alterity within the context of commercial hospitality. The central concept focuses on the genuine experiences of a food and beverage host, underscoring the crucial role of alterity in commercial hospitality. Alterity involves recognising and engaging with the experiences of others, making the concept of “Otherness” essential for fostering positive interactions within this industry. Moreover, the research emerged from a profound understanding of Otherness shaped through careful self-reflection. These insights foster greater self-awareness, enabling individuals to manage and regulate emotions more effectively when faced with overwhelming negative feelings. The ability to navigate these challenging emotions enables frontline hospitality workers to experience authentic joy, rooted in genuine hospitality, which in turn results in meaningful and satisfying experiences within the commercial hospitality sector. This research adopts a phenomenological approach to examine the case of an exuberant host within the food and beverage sector of the hospitality industry. By utilising Interpretative Phenomenological Analysis (IPA) and autoethnography, the study explores the joyful experiences of the enthusiastic host through the lens of Dasein. It highlights key events that evoke a sense of Otherness while providing a comprehensive cultural analysis of personal experiences. The research emphasises the valuable insights gained from a significant event at the Chandelier Lounge in the Cordis Hotel Auckland, which I referred to as the “phenomenon of the tipping flute.” I have interpreted the phenomenon of the tipping flute, which relates to a theory that elucidates the concept of sui generis empathy, acknowledging otherness. This perspective is crucial for food and beverage hosts who consider and integrate this principle into their daily roles. This research asserts that authentic happiness is achievable in the hospitality sector, even when confronted with its most emotionally taxing challenges. Furthermore, while the idea of alterity—recognising ‘Otherness’—is important in commercial hospitality, it warrants further investigation and a more thorough examination. The exploration of the joyful host phenomenon offers a captivating perspective on its application. It highlights a crucial opportunity to nurture a culture of alterity within the industry. The study strongly suggests that adopting the concept of alterity can significantly improve the overall hospitality experience. These insights could motivate the hospitality sector to create a more welcoming and compassionate atmosphere, ultimately contributing to the development of a more empathetic and enjoyable future in the hospitality industry.